Risk of Coronavirus Disease 2019–Associated Pulmonary Aspergillosis Based on Corticosteroid Duration in Intensive Care Patients. (3rd March 2023) - Shah, Meera; Reveles, Kelly; Moote, Rebecca; Hand, Elizabeth; Kellogg III, Dean; Attridge, Rebecca L; Maselli, Diego J; Gutierrez, G Christina
Abstract: Background: Coronavirus disease 2019 (COVID-19)–associated pulmonary aspergillosis (CAPA) is a potential complication in critically ill COVID-19 patients. Corticosteroids are standard of care for hospitalized COVID-19 patients but carry an increased risk of secondary infections including CAPA. The objective of this study was to evaluate if duration of corticosteroid therapy ≤10 days versus >10 days affects the risk of developing CAPA. Methods: This was a retrospective cohort study of adult patients with severe COVID-19 pneumonia requiring mechanical ventilation who received at least 3 days of corticosteroid treatment. Incidence of CAPA and secondary outcomes were compared using appropriate bivariable analyses. Steroid duration was evaluated as an independent predictor in a logistic regression model. Results: A total of 278 patients were included (n = 169 for ≤10 days' steroid duration; n = 109 for >10 days). CAPA developed in 20 of 278 (7.2%) patients. Patients treated with >10 days of corticosteroid therapy had significantly higher incidence of CAPA (11.9% vs 4.1%; P = .0156), and steroid duration >10 days was independently associated with CAPA (odds ratio, 3.17 [95% confidence interval, 1.02–9.83]). Secondary outcomes including inpatient mortality (77.1% vs 43.2%; P < .0001), mechanical ventilation–free days at 28 days (0 vs 1.5; P < .0001), and secondary infections (44.9% vs 28.4% P = .0220) were worse in the >10 days cohort. Conclusions: Corticosteroid treatment >10 days in critically ill COVID-19 patients is associated with an increased risk of CAPA. Patients may require corticosteroids for reasons beyond COVID-19 and clinicians should be cognizant of risk of CAPA with prolonged courses. Abstract : Corticosteroid therapy of >10 days' duration was independently associated with an increased risk of the development of COVID-19–associated pulmonary aspergillosis (CAPA). Critically ill patients may require corticosteroids for reasons beyond COVID-19, and clinicians should be cognizant of risk of CAPA with prolonged courses.